2002
DOI: 10.1007/s00436-001-0552-9
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola gigantica: the growth and larval productivity of redial generations in the snail Lymnaea truncatula

Abstract: Bimiracidial infections of French Lymnaea truncatula with a Madagascan isolate of Fasciola gigantica were carried out under laboratory conditions to study the growth of rediae and their larval productivity in relation to the different redial generations. The total numbers of rediae and their mean lengths significantly increased with the duration of infection until day 49 post-exposure (p.e.). Significant differences in the lengths between the different redial generations were noted. At day 49 p.e. (at 20 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In this intermediate host, up to three redial generations succeed one another (Rakotondravao et al, 1992;Dar et al, 2002). However, these authors found a slow larval development of F. gigantica in French populations of L. truncatula when they used Madagascan isolates of miracidia for their experiments.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this intermediate host, up to three redial generations succeed one another (Rakotondravao et al, 1992;Dar et al, 2002). However, these authors found a slow larval development of F. gigantica in French populations of L. truncatula when they used Madagascan isolates of miracidia for their experiments.…”
Section: Introductionmentioning
confidence: 86%
“…Each snail from the first group was subjected to a bimiracidial infection with the Madagascan isolate, while the L. truncatula from the second and the third groups were individually exposed to bimiracidial infections with Chinese and Egyptian isolates, respectively. They were then raised in open aerated breeding boxes (50 snails per box) for 49 days at 208C under an experimental photophase of 12 h (Dar et al, 2002). Samples of 5 to 10 snails each were taken among the survivors on the following days: 14, 21, 28, 35, 42 and 49 post-exposure (p.e.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bitakaramire in 1968 (a mean of 653 per snail). These differences between cercarial productions of F. gigantica from L. natalensis might partly be due to the geographical origin of the miracidial isolate used for experimental infections (Boray, 1969;Mohamed et al, 1998;Dar et al, 2002), or to the definitive host from which F. gigantica eggs and, consequently, miracidia originated (Al-Kubaisee & Altaif, 1989). However, variability in the susceptibility of L. natalensis populations to F. gigantica infections cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Even though another lymnaeid snail, L. columella (Ahmed & Ramzy, 1999) and a planorbid species, Biomphalaria alexandrina (Farag & El-Sayad, 1995), are also naturally infected with F. gigantica in Egypt, L. natalensis and G. truncatula are responsible for transmitting fasciolosis in most areas of this country (Farag, 1998;El-Shazly et al, 2002). The developmental pattern of F. gigantica redial generations in both these lymnaeids is identical, but the larval production of this trematode in L. natalensis (Dinnik & Dinnik, 1956) differs from that found in G. truncatula (Rakotondravao et al, 1992;Dar et al, 2002). This difference might be due to the isolates of miracidia used, as Dar et al (2003), using three different isolates of F. gigantica originating from China, Egypt and Madagascar, found that larval production was influenced by the origin of the parasite.…”
Section: Introductionmentioning
confidence: 87%